2017
DOI: 10.1089/jpm.2017.0049
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Physicians, Continuity and Coordination of Care, and Quality of Death in Patients with Advanced Cancer

Abstract: Trust of the patient and family in home hospice staff, as well as coordination of care among hospice staff, are associated with the QOD for cancer patients dying at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
10
0
8
Order By: Relevance
“…2 However, although the association between relational continuity and trust has been widely explored, the concept of trust has almost always been the patient trust in the clinician, even where a study purports to explore mutual trust. 32,33 In 2013, a systematic review of clinicianpatient trust found only one study where the explicit focus was GP trust in patients, 34 and one further study has since explored this. 35…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…2 However, although the association between relational continuity and trust has been widely explored, the concept of trust has almost always been the patient trust in the clinician, even where a study purports to explore mutual trust. 32,33 In 2013, a systematic review of clinicianpatient trust found only one study where the explicit focus was GP trust in patients, 34 and one further study has since explored this. 35…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…"Good relations with the family" demonstrates the importance of family support and coexistence and its relationship with dignified death, which is also found in previous research conducted in China 16 , South Korea 24 and Germany 18 . However, in Japanese 25,26 and American 27 studies, family presence was not considered the main factor, but factors such as being free from pain, being at peace with God 12 , being valued as a person 25 and trusting the doctor 26 . While in Brazilian culture and in Asian countries the family occupies a central place, in the United States (USA) and in other western populations individualism is more valued, which justifies the physical and cognitive control at the end of life being more important for them 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in Japanese 25,26 and American 27 studies, family presence was not considered the main factor, but factors such as being free from pain, being at peace with God 12 , being valued as a person 25 and trusting the doctor 26 . While in Brazilian culture and in Asian countries the family occupies a central place, in the United States (USA) and in other western populations individualism is more valued, which justifies the physical and cognitive control at the end of life being more important for them 26 . On the other hand, in this research, the least considered factor of high need was precisely "physical and cognitive control".…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical evidence has demonstrated the benefit of a well-managed and smooth transition to palliative care in terms of quality of life and psychosocial well-being (Kirby et al, 2014), the transition to palliative care is a process that has not been studied extensively (Marsella, 2009; Rocio et al, 2017) and the transition of terminally ill patients is a challenging aspect of clinical work. However, current evidence suggests that continuity of care is the best way to ensure effective palliative care transitions, while also enhancing the quality of the time left to live for patients and their caregivers (Gardiner et al, 2015; Hamano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%